The efficacy and safety of hachimijiogan for mild Alzheimer disease in an exploratory, open standard treatment controlled, randomized allocation, multicenter trial: A study protocol. Issue 38 (18th September 2020) - Kainuma, Mosaburo; Funakoshi, Kouta; Ouma, Shinji; Yamashita, Ken-ichiro; Ohara, Tomoyuki; Yoshiiwa, Aoi; Murata, Masayuki; Tsuboi, Yoshio
Abstract: Background: Dementia among the Japanese aged 65 years or over population is estimated to approach about 700 million cases by 2025, and a corresponding rapid increase in Alzheimer disease (AD) can also be expected. The ballooning number of dementia patients, including AD, is creating major medical and social challenges. At present, only 3 drugs are recognized for the treatment of mild AD, and these are only used to alleviate symptoms. Although new therapies are needed to treat mild AD, insufficient development of disease-modifying drugs is being done. Methods/Design: The aim of this exploratory, open standard, treatment-controlled, randomized allocation, multicenter trial is to determine the efficacy of the traditional Japanese Kampo medicine hachimijiogan (HJG) on the cognitive dysfunction of mild AD. Eighty-six patients with AD diagnosed according to the Diagnostic and Statistical Manual of Mental Disorders (DSM)-5 and as mild AD according to the Mini Mental State Examination (MMSE ≥21) will be included. All will already have been taking the same dose of Donepezil, Galantamine, or Rivastigmine for more than 3 months. The patients will be randomly assigned to receive additional treatment with HJG or to continue mild AD treatment without additional HJG. The primary endpoint is the change from baseline of the Alzheimer's Disease Assessment Scale-cognitive component- Japanese version (ADAS-Jcog). ADAS-Jcog is a useful index for detecting change over time that investigates memory and visuospatial cognition injury from the early stage. The secondary endpoints are the changes from baseline of the Instrumental Activity of Daily Life, Apathy scale, and Nueropsychiatric Inventory scores. In this protocol, we will examine the Geriatric depression scale and do Metabolome analysis as exploratory endpoints. The recruitment period will be from August 2019 to July 2021. Discussion: This is the first trial of Kampo medicine designed to examine the efficacy of HJG for the cognitive dysfunction of patients with mild AD. Trial registration: This trial was registered on the Japan Registry of Clinical trials on 2 August 2, 2019 (jRCTs 071190018).